반응향을 적용한 간장박 가수분해물로부터 Savory Flavor의 생성 - 차용준(Yong-Jun Cha); 왕문봉(Wenfeng Wang) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2018)
간장박 가수분해물에 0.5%의 fructose와 0.33%(w/v)의 glutamic acid, proline 0.99%(w/v), methionine 0.42% (w/v) 및 glycine 0.41%(w/v)를 넣고 93°C에서 120분간 반응향을 유도한 가수분해물(RFT)을 대조구(Control)와 함께 휘발성 향기성분을 분석한 결과, 총 82종의 휘발성 성분이 검출 동정(RFT에서 68종, 대조구에서 59종)되었으며, 방향족화합물(15종), 알데히드 및 케톤화합물(12종), 산류(9종), 알코올류(11종), 에스터류(9종), 퓨란류(9종), 질소 및 황함유화합물류(13종) 및 기타화합물류(4종)로 구성되었다. 퓨란류가 함량면에서는 가장 많았으며(Control: 1,466.38 ng/ g, RFT: 1,011.29 ng/g) 반응향을 통하여 31% 정도 감소하였다. 질소 및 황함유화합물은 반응향을 통하여 65.7배 증가하였다(P<0.05)(Control: 7.86 ng/g, RFT: 516.47 ng). 방향족화합물 및 산류의 함량은 반응향을 통하여 유의하게 감소하였고(P<0.05), 알데히드류는 증가하였다. 특히 3종의 함황화합물인 dimethyl disulfide(상한 양파, sour), dimethyl trisulfide(간장, 조리한 양배추) 및 methional(간장 및 구은 감자향)과 3-methylbutanal 등은 각각 12, 0.01, 0.2 및 0.2 ng/g의 매우 낮은 역치로 인하여 반응향을 통하여 생성된 가수분해물의 savory flavor에 크게 관여할 것으로 생각되었다. Reaction flavored sauce (RFT) was made from hydrolysate of soy sauce residue (Control) by adding 0.5% fructose, 0.33% glutamic acid, 0.99% proline, 0.42% methionine, and 0.41% (w/v) glycine into Control for 120 min at 93°C. The volatile flavor compounds were compared between RFT and Control using solid phase microextraction/gas chromatography/mass selective detector (SPME/GC/MSD). A total of 82 compounds were detected in samples (68 RFT, 59 Control), which were composed of aromatic compounds (15), aldehydes and ketones (12), acids (9), alcohols (11), esters (9), N- and S-containing compounds (13), and miscellaneous compounds (4). Furans were the most abundant (1,466.38 ng/g in Control, 1,011.29 ng/g in RFT) and decreased by 31% after reaction flavor, whereas N- and S-containing compounds increased 65.7 times through reaction flavor (P<0.05). The amounts of aromatic compounds and acids decreased, whereas aldehydes increased (P<0.05). Particularly, three S-containing compounds, including dimethyl disulfide (rotten onion-like, sour, and 12 ng/g threshold), dimethyl trisulfide (soy sauce-like, cooked cabbage-like, and 0.01 ng/g threshold), and methional (soy sauce, baked potato-like, and 0.2 ng/g threshold) formed through reaction flavor contributed to the savory flavor of RFT. KCI Citation Count: 5